Colostro e leite de éguas: análise mirobiológica e contagem de células somáticas - Bernardineli, Ana Paula Bertoni [UNESP] (2014)
Given the importance of colostrum and milk of the mare on feeding and acquisition of immunity of newborn foals and their use in the human diet, the aim of the study was to evaluate the composition, physicochemical properties, microbiological profile and somatic cell count (SCC) of colostrum and milk of mares in early lactation. Samples were collected from 36 mares at seven moments: M1 = moment of partum, M2 = 12 hours, M3 = 24 hours, M4 = 36 hours, M5 = 48 hours, M6 = 11 days and M7 = 15 days post-partum. It was observed decreased levels of protein, fat, total solids and solids non-fat, and increased levels of lactose during the evaluated moments. There was also variation in pH, cryoscopic index and acidity during the moments, especially between samples of colostrum and transitional milk. The microbiological isolation occurred in 5.55% of the cultured samples, of which, 28.57% was non-hemolytic Streptococcus, 28.57% α-hemolytic Streptococcus, 21.43% Streptococcus equi, 14.29% Micrococcus spp. and 7.14% Bacillus spp. No animals showed clinical mastitis. Higher SCC values were found in M1 and M2, with a significant decrease in M3, with values less than 100,000 somatic cells / mL from this moment. Given these results, changes in the composition, physicochemical quality and cellularity during the first 15 days of lactation were observed. Eleven samples were positive on California Mastitis Test, being observed in M1 (36.36%), M2 (27.27%), M3 (18.19%), M5 (9.09%) and M7 (9.09%). Bacteria of the genera Streptococcus were the most frequently isolated. However, caution is needed in the use of some methods for diagnosis of mastitis, because there is no standardization in the equine species